Differences in Tobacco Use Among a Sample of At-Risk Chinese, Filipino, and Vietnamese Adult Men Living in the SF Bay Area. (August 2019) - Toleran, Daniel E; Battle, Robynn S; Gardiner, Phillip
Background: Smoking among Asian men has been studied, but differences in tobacco and cigarette use among US- and non-US-born Asian subgroups, especially those at risk for substance use or sexually transmitted diseases, has not been well-studied. Aims: To learn about the smoking of cigarettes or blunts among Asian ethnic groups, and whether place of birth, age, or primary language spoken at home is associated with smoking. Methods: Study participants were 125 adult (age > 18 years) Chinese, Filipino, or Vietnamese men living in San Francisco, Daly City, or San Jose, California, who self-reported substance use in the past 30 days. Information collected included sexual orientation, past year contact with the criminal justice system, place of birth, and primary language spoken at home. Bivariate analyses were used to compare the differences in self-reported smoking of cigarettes or tobacco-marijuana blunts by ethnicity, age, place of birth, and primary language spoken at home. Results: Filipinos had significantly higher rate of cigarette use (51%; P = .02) and smoking blunts (28%; P = .02) compared with Chinese (23% and 5%, respectively) or Vietnamese (34% and 17%, respectively); US-born Filipinos also had more days of cigarette use in the past 30 days (16 days; P = .05) compared with Chinese (8 days) or Vietnamese (6 days) participants. Conclusions: This study found differences in self-reported rates of cigarette and blunt use among Asian ethnic groups which suggest opportunities for targeted interventions. Future studies of tobacco or blunts use for these largely immigrant groups should take into account country of birth and language spoken at home in developing tobacco prevention services for this population.